Renewable Energy Policies and Programs in Nunavut: Perspectives from the Federal and Territorial Governments - McDonald, Nicole C.; Pearce, Joshua M. (ARCTIC, 2012)
Nunavut, the youngest Canadian territory, has developed a complete dependence on diesel-generated electricity over the last 50 years, which has led to environmental and economic stress on the territory. However, renewable energy technologies (RETs) could provide substantial electricity to communities, thereby reducing the use of diesel fuel. This study explored the perspectives of government policy-makers, northern energy consultants, and NGOs in order to understand the current status of renewable energy policy and development in Nunavut. Challenges identified included capacity gaps within the communities and government, bureaucratic barriers, barriers to financing RET projects, technological uncertainty, and development and infrastructure challenges. Opportunities explored include future RET funding options, strong renewable resources, increased community engagement through partnerships, and increased education opportunities. Respondents also discussed anticipated short- and long-term actions of each department. We recommend the establishment of a clear point of contact within the federal government: a group that would oversee all renewable energy policy and development in Nunavut. The group would also assess the full economic life cycle of renewable electricity to compare its true cost to that of unsubsidized, diesel-generated electricity. Le Nunavut, soit le plus jeune territoire du Canada, a développé une dépendance complète à l’électricité produite à partir du diesel ces 50 dernières années, ce qui engendre du stress environnemental et économique au sein du territoire. Cependant, les technologies des énergies renouvelables (TER) pourraient fournir de bonnes quantités d’électricité aux collectivités, ce qui réduirait la consommation de diesel. Cette étude s’est penchée sur les perspectives des preneurs de décisions des gouvernements, des consultants en énergie du nord et des organismes non gouvernementaux afin de parvenir à comprendre l’état actuel de la politique sur les énergies renouvelables et le ...